Jihadi Intelligence and Counterintelligence - Haberl, Ferdinand J. author. aut Link
XI, 318 p. 7 illus., 2 illus. in color.
Keywords: This book analyzes the ideological roots, structures and operational methods of Jihadi intelligence and counterintelligence activities. Based on a substantive collection of data on terrorist attacks, communication channels, recruitment methods, manuals and statements released by various Jihadi groups, it examines and compares the nature, ideology and realities of Jihadi intelligence operations. The author, an expert on Jihadist ideology and paramilitary intelligence, compares the modus operandi of terrorist groups such as al-Qaeda and the IS with those of governmental intelligence agencies, and subsequently analyzes the role of historical and religious narratives that help Jihadist groups justify their actions and military management. Further topics covered include encryption, counterfeiting, covert operations and Jihadi intelligence activities in the digital realm. The insights shared here will allow readers to gain a comprehensive understanding of Jihadist groups and their intelligence operations, while helping practitioners and policymakers develop better counterterrorism activities and counternarratives.